(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the new words that have entered the Uzbek language due to modern technologies and the changes they have undergone in our language. In particular, many new words have entered Uzbek through the internet and mobile phones, either without modification or by being adapted into Uzbek. The article highlights their impact on the language and the changes taking place.